2008
DOI: 10.1073/pnas.0709338105
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of the plant Medicago truncatula to its symbiont Sinorhizobium meliloti or an exopolysaccharide-deficient mutant

Abstract: Sinorhizobium meliloti forms symbiotic, nitrogen-fixing nodules on the roots of Medicago truncatula. The bacteria invade and colonize the roots through structures called infection threads. S. meliloti unable to produce the exopolysaccharide succinoglycan are unable to establish a symbiosis because they are defective in initiating the production of infection threads and in invading the plant. Here, we use microarrays representing 16,000 M. truncatula genes to compare the differential transcriptional responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
119
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(128 citation statements)
references
References 51 publications
7
119
0
2
Order By: Relevance
“…For nodulation efficiency, RhiI synthesized C6HSL, C7HSL and C8-HSL activate the rhiABC genes. These QSS also govern motility and exopolysaccharide production which is required for infection process, and biofilm formation [80,81]. In Sinorhizobium meliloti, sinI/ sinR and expR, regulate the Sin QSS through long chain AHLs: C12HSL to C18HSL [29,[82][83][84].…”
Section: Rhizobiummentioning
confidence: 99%
“…For nodulation efficiency, RhiI synthesized C6HSL, C7HSL and C8-HSL activate the rhiABC genes. These QSS also govern motility and exopolysaccharide production which is required for infection process, and biofilm formation [80,81]. In Sinorhizobium meliloti, sinI/ sinR and expR, regulate the Sin QSS through long chain AHLs: C12HSL to C18HSL [29,[82][83][84].…”
Section: Rhizobiummentioning
confidence: 99%
“…The transcriptomic data showed that S.meliloti exoY minus mutant (not synthesize succinoglycan) induced the elevated expression of many defense related genes on host M. truncatula, suggesting that succinoglycan suppresses host immunity during infection. 17 Whether the oligomer of EPS is perceived by a receptor, interacting with MAPKs to constitute a signaling pathway will be elucidated by forward genetics and biochemistry.…”
Section: It Is Interesting That Purified Lps Frommentioning
confidence: 99%
“…Of particular interest are studies that used mutant strains of rhizobia to dissect the transcriptional changes associated to recognition of signal molecules from bacteria. 28,[30][31][32][33] (Table 1). Jones and collaborators 32 showed the differences in the M. truncatula transcriptional response when it was inoculated with the wild type strain or a succinoglycan-deficient strain of S. meliloti unable to establish a successful infection.…”
mentioning
confidence: 99%
“…28,[30][31][32][33] (Table 1). Jones and collaborators 32 showed the differences in the M. truncatula transcriptional response when it was inoculated with the wild type strain or a succinoglycan-deficient strain of S. meliloti unable to establish a successful infection. The absence of this exopolysaccharide resulted in a reduction of genes involved in protein synthesis and degradation, as well as genes involved in nodulation (known as nodulins).…”
mentioning
confidence: 99%